The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1104/pp.111.3.805
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alteration of Polyunsaturated Fatty Acid Levels on C6-Aldehyde Formation of Arabidopsis thaliana Leaves

Abstract: C,-aldehydes are synthesized via lipoxygenase/hydroperoxide lyase action on polyunsaturated fatty acid (PUFA) substrates i n plant leaves. The source pools and subcellular location of the processes are unknown. A close relationship is found between the composition of PUFA and the composition of C,-aldehydes. I n the current study, this relationship was tested using the Arabidopsis PUFA mutant lines actl, fad2, fad3 fad5, fad6, and fad7. The results indicate that C,-aldehyde formation is influenced by the alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
2
11
0
Order By: Relevance
“…Previous studies indicate that chloroplast targeting peptides are present on AOS from flax and Arabidopsis (Song et al, 1993;Harms et al, 1995;Laudert et al, 1996), as well as HPL from Arabidopsis (Bate et al, 1998). A plastid location for AOS and HPL is consistent with biochemical studies demonstrating that AOS and HPL activity is associated with chloroplasts (Vick and Zimmerman, 1987;Gardner et al, 1991;Blée and Joyard, 1996;Zhuang et al, 1996). Recently, we have shown that LeAOS is imported into chloroplasts where it specifically targets to the inner membrane of the chloroplast envelope (Froehlich et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies indicate that chloroplast targeting peptides are present on AOS from flax and Arabidopsis (Song et al, 1993;Harms et al, 1995;Laudert et al, 1996), as well as HPL from Arabidopsis (Bate et al, 1998). A plastid location for AOS and HPL is consistent with biochemical studies demonstrating that AOS and HPL activity is associated with chloroplasts (Vick and Zimmerman, 1987;Gardner et al, 1991;Blée and Joyard, 1996;Zhuang et al, 1996). Recently, we have shown that LeAOS is imported into chloroplasts where it specifically targets to the inner membrane of the chloroplast envelope (Froehlich et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…The spr2 mutation in tomato also alters the profile of C6 volatile organic compounds (VOCs) generated from linoleic acid (C18:2) and linolenic acid (C18:3) via the hydroperoxide lyase pathway (HPL), resulting in a dramatic increase in hexanal and hexanol production and a decrease in (Z)-3-hexenal and (Z)-3-hexanol (Canoles et al, 2006;Sánchez-Hernández et al, 2006). Similar shifts in volatile profiles were also observed in Atfad7 Arabidopsis plants (Zhuang et al, 1996), although overall production of C6 volatiles is reported to be extremely low in the Columbia ecotype (Duan et al, 2005;Chehab et al, 2008). HPL appears to contribute to aphid resistance in potato (Vancanneyt et al, 2001), and several VOCs have direct antibiotic effects on aphids in vitro (Hildebrand et al, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…Figure 6 shows the levels detected in triplicate tissue extracts. As described for dicotyledon leaf tissues [35–37] (3 Z )‐ plus (2 E )‐hexenal were found to be the major aldehydes in barley leaves. Upon treatment of leaf segments with JAME, a transient maximum at 24 h was detected.…”
Section: Resultsmentioning
confidence: 65%